Analysis of Local Tax Potential of Ogan Komering Ulu Regency - Zega, Elsa Calista; Hardiana, Nadhira (Yayasan Ilomata, 2024)
The original revenue of local governments is one of the vital elements that can support regional development and governance, exemplified by BPHTB as a significant revenue generator. This study aims to analyze the potential of the Fees for Acquisition of Rights on Land and Buildings (BPHTB), which is one of the local taxes in the Ogan Komering Ulu Regency. The research employs a qualitative approach with descriptive methods. The discussion reveals that the regional original revenue in Ogan Komering Ulu Regency experiences significant fluctuations but generally increases annually. This phenomenon is attributed to the efforts of related institutions in collecting and implementing policies to optimize the original revenue. The implementation of the BPHTB tax policy along with existing policies in Ogan Komering Ulu Regency has caused some challenges as it was considered a panic policy following the audit conducted by the BPK. However, ultimately, this policy has contributed to an increase in original revenue through the enforcement of the applicable land tax.